Penerapan Theory of Constraints (TOC) untuk Meningkatkan Kapasitas Produksi dan Laba Perusahaan: (Studi Kasus pada UMKM Keripik Sari Asih) - Ghina Hamidah; Hastuti, Hastuti (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to apply the Theory of Constraints (TOC) in overcoming the constraints that exist in the research object of UMKM Keripik Sari Asih which in the production process can only fulfill 77% to 81% of the total demand in October and November 2022. Theory of Constraints is a theory which can assist companies in overcoming existing obstacles to increase company profits. This research method uses a qualitative method by describing the facts and theories used, then processed and analyzed in the form of words. Data collection techniques were carried out by means of interviews, observation, and documentation. The application of TOC goes through the stages of identifying constraints, then exploiting the constraints, then subordinating it to other sources. If the obstacle has not been resolved, then evaluate the obstacle, but if it has been resolved, go to the final stage, which is to repeat the whole process. The results showed that there were obstacles in the process of cutting cassava chips, the comring molding process, and the frying process. After analysis, the selected alternative for solving the constraints is to buy one unit of cutting equipment, add 150 minutes of work shift, and buy one unit of fryer, this alternative can increase production capacity and profit